Induction of Systemic Resistance against Aphids by Endophytic Bacillus velezensis YC7010 via Expressing PHYTOALEXIN DEFICIENT4 in Arabidopsis - Rashid, Md. Harun-Or-; Khan, Ajmal; Hossain, Mohammad T.; Chung, Young R. (Frontiers in Plant Science, 2017)
Aphids are the most destructive insect pests. They suck the sap and transmit plant viruses, causing widespread yield loss of many crops. A multifunctional endophytic bacterial strain Bacillus velezensis YC7010 has been found to induce systemic resistance against bacterial and fungal pathogens of rice. However, its activity against insects attack and underlying cellular and molecular defense mechanisms are not elucidated yet. Here we show that root drenching of Arabidopsis seedlings with B. velezensis YC7010 can induce systemic resistance against green peach aphid (GPA), Myzus persicae. Treatment of bacterial suspension of B. velezensis YC7010 at 2 × 107 CFU/ml to Arabidopsis rhizosphere induced higher accumulation of hydrogen peroxide, cell death and callose deposition in leaves compared to untreated plants at six days after infestation of GPA. Salicylic acid, jasmonic acid, ethylene and abscisic acid were not required to confer defense against GPA in Arabidopsis plants treated by B. velezensis YC7010. Bacterial treatment with B. velezensis YC7010 significantly reduced settling, feeding and reproduction of GPA on Arabidopsis leaves via strongly expressing senescence-promoting gene PHYTOALEXIN DEFICIENT4 (PAD4) while suppressing BOTRYTIS-INDUCED KINASE1 (BIK1). These results indicate that B. velezensis YC7010-induced systemic resistance to the GPA is a hypersensitive response mainly dependent on higher expression of PAD4 with suppression of BIK1, resulting in more accumulation of hydrogen peroxide, cell death and callose deposition in Arabidopsis.